2012
DOI: 10.1186/1476-069x-11-s1-s8
|View full text |Cite
|
Sign up to set email alerts
|

Environmental exposure to xenoestrogens and oestrogen related cancers: reproductive system, breast, lung, kidney, pancreas, and brain

Abstract: The role of steroids in carcinogenesis has become a major concern in environmental protection, biomonitoring, and clinical research. Although historically oestrogen has been related to development of reproductive system, research over the last decade has confirmed its crucial role in the development and homeostasis of other organ systems. As a number of anthropogenic agents are xenoestrogens, environmental health research has focused on oestrogen receptor level disturbances and of aromatase polymorphisms. Oest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 121 publications
0
79
0
4
Order By: Relevance
“…Introduced to environment they cause a lot of unfavourable changes observed especially among animals living in marine and inland waters, such as malformation of sexual features, fertility disruptions and in consequence dying out of some species of bivalves, amphibians, fishes and mammalians [7][8][9][10]. The occurrence of xenoestrogens in drinking water can result in a wrong form of sex in the foetal period of humans and lead to cancer genesis [11][12][13]. For this reason, alachlor like most xenoestrogens was included in the European Union legislation [14] and Polish legislation [15 ] as a hazardous priority substance, which should be totally eliminated from environment.…”
Section: Introductionmentioning
confidence: 99%
“…Introduced to environment they cause a lot of unfavourable changes observed especially among animals living in marine and inland waters, such as malformation of sexual features, fertility disruptions and in consequence dying out of some species of bivalves, amphibians, fishes and mammalians [7][8][9][10]. The occurrence of xenoestrogens in drinking water can result in a wrong form of sex in the foetal period of humans and lead to cancer genesis [11][12][13]. For this reason, alachlor like most xenoestrogens was included in the European Union legislation [14] and Polish legislation [15 ] as a hazardous priority substance, which should be totally eliminated from environment.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, regulations on pollutants should take into account new scientific evidences on age and gender differential susceptibilities [105,106].…”
Section: Resultsmentioning
confidence: 99%
“…Increase of cancer incidence and change in its age and gender [1][2][3][4][5][6] distribution during the last few decades can be attributed to better diagnostics but also to exposure to new risk factors, including xenobiotics, introduced to our living environment. Additionally, most investigations and risk assessments did not, or could not, take into account gender and age of subjects at the time of exposure to early risk factors; this knowledge gap on a critical phase of the dynamic of carcinogenesis reduces the accuracy and reliability of current assessments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have reported that they act mainly by an in--vivo mechanism mediated by the estrogen receptor (ER). [11][12][13]21 Although parabens have been termed "weak estrogens" because of their low--binding affinity to the ER, their level of response to the growth of human breast cancer cells in vitro may be the same as that of 17β -estradiol when sufficient concentrations are present. 21 The estrogenic activity of some cosmetic products with parabens has recently been confirmed again by the development of gynecomastia in 3 prepubertal boys as a consequence of the topical application of body oils.…”
Section: -6mentioning
confidence: 99%